Application of fractional order iterative learning controller for a type of batch bioreactor. Issue 12 (1st August 2016) - Rezaei Estakhrouiyeh, Mohsen; Vali, Mohammadali; Gharaveisi, Aliakbar
Abstract : In this study, a fractional order iterative learning controller (FOILC) is designed for a non‐linear fractional order bioreactor system. Bioreactors are widely used in horticulture, medical plants, tissue engineering, waste water recycling, biomass production and many other applications. Since fed‐batch systems are repetitive processes and some specific types have fractional dynamics, FOILC algorithm is workable for them. This research shows, via simulations, the benefits of using FOILC along with a robust fractional order PID (FOPID) to attain both robustness and precision tracking for the bio‐reactor system. This leads to better product quality and more flexibility, since the system can learn the new dynamics after a few iterations, in case of plant changes, besides getting better disturbance rejection against repetitive and non‐repetitive disturbances.